Effects of nutrient (N, P, K) fertilization on the dynamics of fine roots in tropical rain forests with different soil texture in the Colombian Pacific region - Quinto Mosquera, Harley; Moreno Hurtado, Flavio H. (Revista de Biología Tropical, 2022)
Introduction: Fine root dynamics include production, turnover and decomposition; they are crucial to forest health, affect the entire biogeochemical complex of the ecosystem, and consequently, they substantially affect carbon balance. However, the influence of environmental factors and soil nutrient limitation on fine roots presents considerable uncertainties and has not been studied in tropical forests with more than 7 000 mm annual rainfall. Objective: To measure the effect of fertilization on fine roots in the high precipitation Chocó forest. Methods: We worked in two sites of the Chocó region, Colombia (August 2014-May 2015), where rainfall exceeds 10 000 mm per year. We applied five fertilization treatments (N, P, K, NPK and Control) to two soil type plots. Soil cylinders were removed at pre-established intervals to measure roots. Results: Phosphorus applications increased fined roots; and more fine roots were produced in sandy than in loam soil. The effects of fertilization were related, but not clearly determined by edaphic conditions. Conclusions: In this Chocó forest, the production of fine roots was higher in sandy and nutrient-rich soils but belowground net primary productivity was limited by the content of edaphic Phosphorus.